Urban development and tourism planning reality in the province of M’sila: a case study of Bousaada city – Algeria - Barkat , Zine Elabidine (Technium Social Sciences Journal, 2022)
Tourism is a vital economic resource that can’t be excluded from government economic policies. In many countries, tourism is one of the most important sources of income for the local economy. In addition, urban development specialists consider tourism as a factor activating the city’ s urban dynamics, through the creation of new income sources, i.e. the support of urban economy and the development of infrastructures, the creation of specific and quality local services, the establishment and structuring of broad social and cultural relations, etc. The province of M’sila and the city of Bousaada became a known tourist destination that counts high tourist numbers every year since the French occupation. Consequently, it is necessary to understand and identify the tourism reality of this city to assess its current situation. The diagnosis is based on the inventory and evaluation of the various sites and tourist attractions available, both natural and archaeological.